2011
DOI: 10.1007/s13304-011-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

Features of papillary thyroid carcinoma in patients older than 75 years

Abstract: The aim of this study was to evaluate the prognosis in elderly patients affected by papillary thyroid carcinoma. A retrospective review was conducted on 1,407 patients operated on for papillary thyroid carcinoma at our Department from 1990 to 2007. We analyzed the frequency, the stage, the treatment, the recurrence and the survival in a group of patients aged 75 years or more when compared with a group of patients younger. Among 1,407 patients affected by papillary thyroid carcinoma, 117 (8.3%) were older than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…In contrast to patients aged below 60 years, the pathological positive neck nodes were significantly higher in patients aged above 60 years, owing to the presence of lymphovascular space invasion, multifocality, and aggressive histopathological variants in elderly patients, which supports the routine use of lateral neck dissection in this age group 15,16…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to patients aged below 60 years, the pathological positive neck nodes were significantly higher in patients aged above 60 years, owing to the presence of lymphovascular space invasion, multifocality, and aggressive histopathological variants in elderly patients, which supports the routine use of lateral neck dissection in this age group 15,16…”
Section: Discussionmentioning
confidence: 72%
“…Nevertheless, female-to-male ratio seems to decline with the process of aging [45]. Importantly, the mortality rate of PTC is usually higher in the elderly [46]. Presumably, it is a consequence of increased mitotic activity of these tumors and increased likelihood of distant metastases [46].…”
Section: Introductionmentioning
confidence: 99%
“…18,20 Although some studies reported higher frequency of MTC in patients older than 75 years others reported no difference. 12,[20][21][22][23] Likely, authors did not find any difference in MTC between geriatric and nongeriatric patients in this study.…”
Section: Discussionmentioning
confidence: 99%